Potensi Ekowisata Air Panas Di Negeri Nalahia Pulau Nusalaut Kabupaten Maluku Tengah - Tambunan, Nover; Lelloltery, Henderina; Seipalla, Billy B (Universitas Pattimura, 2023)
This study aimed to determine the potential for hot spring ecotourism in Nalahia village on Nusalaut Island, Central Maluku Regency. The method used is direct observation (survey method). Data was collected on all-natural tourist attractions through fauna data around hot springs. Tourist data collection is done by conducting interviews using a questionnaire for tourists with accidental sampling. Data were analyzed using descriptive analysis of tourism potential in hot springs attractions and tourists visiting Nalahia hot springs. The results showed that hot water attractions in Nalahia country are found in two places, namely